2005
DOI: 10.1007/s00425-005-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Two cell wall associated peroxidases from Arabidopsis influence root elongation

Abstract: Two class III peroxidases from Arabidopsis, AtPrx33 and Atprx34, have been studied in this paper. Their encoding genes are mainly expressed in roots; AtPrx33 transcripts were also found in leaves and stems. Light activates the expression of both genes in seedlings. Transformed seedlings producing AtPrx33-GFP or AtPrx34-GFP fusion proteins under the control of the CaMV 35S promoter exhibit fluorescence in the cell walls of roots, showing that the two peroxidases are localized in the apoplast, which is in line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(145 citation statements)
references
References 30 publications
12
131
0
2
Order By: Relevance
“…S9). Peroxidases, which can function to polymerize cell wall compounds, were also up-regulated in TZP-OX, consistent with their role in growth and cell wall expansion (26). Peroxidases PER27, PER30, and PER64 have been shown to be part of the cell wall proteome (27) (six PER genes total; Fig.…”
Section: Tzp Controls Morning-specific Growth Through An Auxin-relatedsupporting
confidence: 55%
“…S9). Peroxidases, which can function to polymerize cell wall compounds, were also up-regulated in TZP-OX, consistent with their role in growth and cell wall expansion (26). Peroxidases PER27, PER30, and PER64 have been shown to be part of the cell wall proteome (27) (six PER genes total; Fig.…”
Section: Tzp Controls Morning-specific Growth Through An Auxin-relatedsupporting
confidence: 55%
“…Studies of individual AtPrx genes suggest that they may be involved in both cell growth and lignification. For instance, abnormal root lengths of the atprx33 and atprx34 mutants point to a role for the corresponding wild-type genes in cell elongation (Passardi et al, 2006), and expression patterns for AtPrx47, AtPrx64, and AtPrx66 are consistent with roles in vessel (AtPrx47, AtPrx64) and sclerenchyma (AtPrx64) lignification (Tokunaga et al, 2009).…”
Section: Peroxidases and Laccasesmentioning
confidence: 93%
“…Recently it was shown that two homologous cell wall-located enzymes POX33 and POX34 are involved in growth-promoting local redox changes in Arabidopsis roots (Passardi et al 2006). Moreover, it was shown that NADPH oxidases are engaged in ROS generation participating in process of the microtubule depolymerization and organization of the cytoskeleton during root hairs growth (Yao et al 2011).…”
Section: Introductionmentioning
confidence: 99%